ANALYSIS OF COMMUNITY AND VILLAGE GOVERNMENT PARTICIPATION IN VILLAGE FUND MANAGEMENT - Erwin Putubasai (University of Sang Bumi Ruwa Jurai, 2018)
The participation of the community and the role of village government in managing the Village Funds initiated in order to build Indonesia through rural or suburbs is the type of fund used for community-based development. Community-based development can be defined as development that refers to community needs, planned, and implemented by the community by maximizing the potential resources (nature, human, institutional, socio-cultural values) that exist and can be accessed by the community local. The participation of the community through the deliberation of development planning in planning the use of the village funds is expected to absorb village funds will eventually really touch the public interest. The purpose of this research is to know and analyze the participation of the community and the role of village government in managing the village funds.The results of the research indicate that: a) Stages of development planning deliberations have indeed been implemented but are still in the phase of collecting problems in the village and summarized in the Village Government Work Plan (namely Rencana Kerja Pemerintah Desa or RKPDesa in Indonesian) and most have not been implemented. b) a large part of the use of the Village Fund is absorbed in the physical development of village infrastructure and infrastructure facilities and only a small percentage of village funds are absorbed in the field of community empowerment and community development.